Root Coverage Procedures: A Case Series - Prachi Khuntia1 , RashmitaNayak2 , Abhaya Chandra Das3, Rinkee Mohanty4 , Saurav Panda3 , Sharmistha (Indian Journal of Forensic Medicine & Toxicology, 2020)
Gingival recession can be defined as the progressive loss of gingival soft tissues. Most of the recession casescan lead to root exposure, interdental bone loss, mobility of teeth. The defect can involve one or multipleteeth. Eventually it progresses towards the root hypersensitivity and tooth loss due to mobility. Recessioncan be treated via using different treatment modalities, by using gingival grafting and regeneration. Graftingprocedure entails to harvesting the tissue from donor sites and suturing it back to the area of recessionfor root coverage. For regeneration purposes, various biomaterials are used with improved properties.Techniques involved in gingival grafts and regeneration involves free gingival grafts, coronally advancedflaps, guided tissue regeneration, etc. This case series reports the effectiveness of various techniques forvestibular deepening along with root coverage, removing the frenum pool along with increasing the widthof the attached gingiva, etc.